Skin Test for Cutaneous Adverse Drug Reactions - Yusuf Wibisono; Damayanti Damayanti (Faculty of Medicine, Universitas Airlangga, 2020)
Background: The incidence of drug eruptions is increasing during the last few years due to a large number of new medications. Early detection of the causative agent and the prevention from exposure are crucial managements in terms of drug eruption, mainly to prevent its recurrence. Objective: To understand skin test as a diagnostic modality in drug eruption, which includes skin patch test, skin prick test, and intradermal test. Literature review: Drug eruption is a form of skin eruption triggered by the use of medications, topical or systemic, in the right dose and indication. The manifestation can vary from maculopapular, urticaria, pustular, and bullous eruption; from the most nonsignificant to a life-threatening reaction. A diagnostic procedure is critical to discover the type of drugs that cause the eruption, i.e., skin test, specific IgE measurement, histamine-release test, and provocation test. Skin test is the first choice in the diagnostic process as it is simple, easy, practical and has high sensitivity and specificity. Conclusion: Skin test is one of the many available diagnostic tools. However, both false positive and false negative results might still arise. The experts are currently attempting to come up with more accurate and practical tests to aid the diagnostic of drug eruption, thus preventing its occurrence.